Los refugiados en Colombia en el marco de los derechos humanos (2020)
Refuge is a state of persons within international law that comprises a great variety of complex elements, which converge on how such persons are seen in the eyes of countries in their legal frameworks and international organizations. In this sense, this study is developed in order to analyze the legal reality of Refugees in Colombia in the face of the human rights protection system. The methodology is developed from a qualitative perspective, this being a study of a documentary nature. The results found allow us to conclude that the various meanings in relation to asylum. This, because in the case of Latin America there is a restricted conception of asylum, since in various international instruments it is conceived as a human right, within which the prior request made by the individual depends for its exercise, for later the analysis is made on behalf of the territorial State and based on its national sovereignty decide.